Biocontrol of Meloidogyne incognita (Kofoid and White) Chitwood, with the application of biological control agents - Pérez-González, Jesús; Bravo-Delgado, Humberto; Tamayo, Yonger; Mendoza, Adolfo; León de la Rocha, Jorge (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2026)
The objective of the research was to determine the potential of Trichoderma spp. strains, Isaria fumosorosea, and Isaria javanica as biocontrol agents against Meloidogyne incognita (Kofoid and White) Chitwood, obtained from tomato cv. Saladette (Solanum lycopersicum L.). Strains of T. harzianum, T. viride, T. koningii, T. asperellum, and a Trichoderma sp. isolate, as well as I. fumosorosea and I. javanica, were used. These were previously selected for their high parasitic capacity, antibiosis, and adaptation to diverse environmental conditions and substrates. In the in vitro assays, parasitism of the biological control agents (a pure filtrate of each strain) on eggs, oothecae, and juveniles (J2) of M. incognita was evaluated. Observations were carried out using an optical microscope with a 40X objective lens at 10 days and 72 hours, respectively. Nematodo control under semi-controlled conditions was conducted in an experimental area using 10 kg polyethylene bags, inoculated with approximately 5,000 juveniles (J2) and planted with tomato seedlings. Seven days after nematode inoculation, the biological agents were applied to the soil; 45 days later, incidence and severity variables were evaluated. Based on the results obtained, it was found that the strains of T. harzianum, T. asperellum, T. koningii, and I. fumosorosea are efficient for the control of different stages of the biological cycle of M. incognita.